Perbandingan Nilai Risk Malignancy Index Kanker Ovarium Tipe Serosum dan Musinosum RSUP Dr. M. Djamil Padang pada Tahun 2017 - Frita Dwi Luhuria; Defrin Defrin; Andi Friadi (Andalas Obstetrics And Gynecology Journal, 2020)
The Risk Malignancy Index (RMI) is one of the simplest assessments that can assist in diagnosing and determining the prognosis of benign and malignant adnexa masses. Epithelial carcinoma is the most common type of about 90% of ovarian cancers.  As many as 35-40% of the epithelial type are serous and 6-10% are musinosum.This study aims to compare the picture of RMI value on the incidence of ovarian cancer serosum and musinosum type. This study was cross sectinal comparative study from medical records of ovarian cancer patients at obstetrics and gynecology section in DR M Djamil Hospital Padang from January 1st, 2017 until December 31st, 2017. The population was found one hundred and forty of patients with ovarian cancer and only one hundred and twenty nine of patients met the inclusion criteria and there were no exclusion criteria. Next RMI value is calculated based on RMI 1 formula, result is described in tabular form and data processing with SPSS program. Conclucion of this study is there were no differences in age distribution, ascites occurrence and age of menopause in serous and musinosum ovarian cancer. There is a difference in Ca, 125 levels in serous with musinosum ovarian cancer which also contribute to the high value of RMI. The mean value of patients‘s RMI in serous type ovarian cancer is higher than the mean value of RMI in patients with type Musinosum ovarian cancer. Keywords: index of risk malignancy, menopause, ultrasonography, anatomic pathology, serous ovarian carcinoma